Normalizing Desire: Stigma and the Carnivalesque in Gay Bigmen's Cultural Practices. (October 2013) - Whitesel, Jason; Shuman, Amy
Girth & Mirth (G&M) is a social group for big gay men who face exclusion and discrimination from both mainstream and gay communities. Based on extensive ethnographic research and interview data, we consider a variety of the group's activities, including gatherings at coffeehouses, participation in a gay pride parade, and a national carnivalesque weekend retreat. The group engages in performances that are complicit with both heteronormative gender practices and normative gay men's practices and that reinscribe capitalist commodified desires. This exploration of the full range of G&M's activities, from the everyday to the carnivalesque, provides an opportunity to examine how a stigmatized group negotiates visible and less visible forms of discrimination through a playful reconfiguration of heteronormative masculine performances.